Study of Water Retention Measurement on Concrete Using Paper Filter Whatman No.42 - Deris Faisa Ralindra; Ria Asih Aryani Soemitro; Indarto Indarto; Ridho Bayuaji (Institut Teknologi Sepuluh Nopember, 2019)
This study aimed to know water retention on concrete using paper filter Whatman No.42. The study was conducted as experimental in laboratory by making two types of specimen with different Water Cement Ratio (WCR); 0.5 and 0.6. Each specimen was immersed for 28 days. Next step was finding the time of consistency water content on specimen and paper filter. Then, water retention could be measured. As a validation of water retention measurement, so the results were compared with saturated salt solution method in dessicator. This study used NaCl, KCl, and H2SO4 as saturated salt solution. The results of water retention measurement were shown in graphs